Nickel: The new EU food safety regulation and what it means for the cacao and chocolate sector - Atkinson, Rachel; Chavez Navarrete, Eduardo Francisco; Da Silva, Mayesse Aparecida; Dekeyrel, Jesse; Giraldo Carvajal, Maria Camila; Martin Lopez, Javier Mauricio; Pulleman, Mirjam; Smolders, Erik; Taborda Lozada, Darlley Stiven; Thomas, Evert (2025)
Nickel levels in chocolate and 14 other food groups will be regulated for the EU market from 1 July 2025 due to potential health risks. Nickel is a metallic element that is found in Earth's mantle, that comes to the crust along tectonic plate boundaries and may enter the food chain due to natural and anthropogenic processes. Nickel is an essential nutrient for plants and used in seed germination, so nuts, seeds, or beans (including cocoa) will always contain some nickel. Data from 359 chocolate bars and nearly 3000 trees from across the world suggest that the new maximum regulated limits are mostly met. Chocolate with higher levels of nickel comes from specific areas and appears related to their geological origin. Reducing nickel uptake by cacao is unlikely to be easy, but liming may be helpful if the soils are high in nickel and acidic. Applying silicates should be avoided. For single-origin or bean-to-bar chocolate, it will be important to map nickel at a farm level to understand whether the mixing of beans or new recipes will be effective for compliance.